Aquatic hazard assessment of MON 0818, a commercial mixture of alkylamine ethoxylates commonly used in glyphosate‐containing herbicide formulations. Part 2: Roles of sediment, temperature, and capacity for recovery following a pulsed exposure. (30th August 2016) - Rodriguez‐Gil, Jose L.; Prosser, Ryan; Hanta, Gregory; Poirier, David; Lissemore, Linda; Hanson, Mark; Solomon, Keith R.
Abstract: A series of toxicity tests with MON 0818, a commercial surfactant mixture of polyoxyethylene tallow amines, were performed: 1) in the presence of sediment for benthic invertebrates and fish: 2) to examine the recovery capacity of Daphnia magna and 4 primary producers after a pulsed (24‐h) exposure; and 3) to examine the potential effect of increased water temperature on toxicity of MON 0818 to 2 cold‐water fishes. In the presence of sediment, no acute (24‐h) mortality was observed for 3 of the 5 species up to 10 mg L −1 . The median effective concentrations for the other 2 species were significantly greater than for water only tests. The EC50 at 15 °C for Salvelinus alpinus was statistically lower than that at 10 °C. Latent effects of a 24‐h exposure (1 mg L −1 ) were observed for Rhabdocelis subcapitata and Chlorella vulgaris, as indicated by delayed growth during recovery phase; however, both cultures were able to recover, as indicated by a lack of changes in maximum absolute growth rates. No significant effects of a 24‐h exposure to MON 0818 were observed for Oophila sp. (1.5 mg L −1 ) or Lemna minor (100 mg L −1 ). Latent mortality after a 24‐h exposure to 5 mg L −1 was observed during the recovery phase for D. magna ; however, reproduction endpoints on surviving individuals were not altered. The results indicate that quick dissipation of MON 0818 in the presence of sediment can reduce the effects on exposed organisms, and that full recovery from 24‐h exposures to concentrations of MON 0818 equal to, or greater than, those expected in the environment is possible. Environ Toxicol Chem 2017;36:512–521. © 2016 SETAC